Pengaruh Keputusan Kultural Majelis Rakyat Papua Nomor III/ KK-MRP/2009 Tentang Kebijakan Khusus dalam Rangka Keberpihakan, Perlindungan dan Pemberdayaan Orang Asli Papua Terhadap Kinerja Kerja Pemerintahan Daerah - Markus Ningmabin (PRANATA HUKUM, 2012)
The influence of cultural decision-Papuans People Assembly (MRP) Papua as a material consideration in determining and implementing the regional administration in terms of empowerment, protection and favor of indigenous Papuans in the container of the Republic of Indonesia Act No. 21 of 2001 about Special Autonomy for the Papuaâs Province as amended by the constitution of the Republic of Indonesia Number 35 Year 2008 on Special Autonomy for Papua and West Papua Province, These results indicate that the decision of the Papuans People Assembly doesnât affect the government policy whichÂ leads to the protection, empowerment and alignments of the indigenous Papuans, because ofÂ most the material that is clearly making a process delegation of law before the decision was made without the involvement of MRP in 2008 because there is no legal instrument on the mechanism of inter-institutional superstructure while the local government after the MRPs decision in 2010 and 2011 cannot describe the regulations that have been made and other materials for regulatory policy collided with a political agenda such as the election of members of the MRP and the election of Governor.